2014
DOI: 10.4238/2014.september.29.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of different ways of transplanting bone marrow mesenchymal stem cells in cardiopulmonary resuscitation in rats

Abstract: ABSTRACT. The effect and mechanism of different ways of transplanting bone marrow mesenchymal stem cells (MSCs) were explored for treating cardiopulmonary resuscitation in a rat model. Rats were divided into the cardiopulmonary resuscitation group (Group Con), the stereotactic lateral ventricle transplantation group (Group LV), the internal carotid artery transplantation group (Group A), and the femoral vein transplantation group (Group V). MSCs were transplanted in Groups LV, A, and V. The MSC transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…18, 19 Considering the advantage of neural stem cells for the treatment of brain damage, 20 we previously showed therapeutic benefits of transplantation of naive BMMSCs for suppressing CA-GCII in rats. 11, 21, 22 The observations from us as well as other groups suggest that increased expression of both BDNF and VEGF by the transplanted BMMSCs, at least in part, contribute to their neuroprotective activities. 11, 23 Furthermore, in our studies we found that, although direct lateral ventricular administration of BMMSCs provided highest efficiency to deliver the cells into the injured brain and to demonstrate the benefits, 11 the operational procedures were invasive and more complicated than the venous approach.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…18, 19 Considering the advantage of neural stem cells for the treatment of brain damage, 20 we previously showed therapeutic benefits of transplantation of naive BMMSCs for suppressing CA-GCII in rats. 11, 21, 22 The observations from us as well as other groups suggest that increased expression of both BDNF and VEGF by the transplanted BMMSCs, at least in part, contribute to their neuroprotective activities. 11, 23 Furthermore, in our studies we found that, although direct lateral ventricular administration of BMMSCs provided highest efficiency to deliver the cells into the injured brain and to demonstrate the benefits, 11 the operational procedures were invasive and more complicated than the venous approach.…”
Section: Resultsmentioning
confidence: 74%
“…11, 21, 22 The observations from us as well as other groups suggest that increased expression of both BDNF and VEGF by the transplanted BMMSCs, at least in part, contribute to their neuroprotective activities. 11, 23 Furthermore, in our studies we found that, although direct lateral ventricular administration of BMMSCs provided highest efficiency to deliver the cells into the injured brain and to demonstrate the benefits, 11 the operational procedures were invasive and more complicated than the venous approach. Despite a high proportion of pulmonary retention, 24 certain number of BMMSCs administered intravenously still successfully migrated into lesioned zones of the brain with CA-GCII, particularly in the hippocampus and cortex.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations